Modification of cardiovascular disease risk by health behaviour change following type 2 diabetes diagnosis. Issue 10 (26th July 2021) - Estlin, Annabel F. L.; Ahern, Amy L.; Griffin, Simon J.; Strelitz, Jean
Abstract: Aims: Among adults with type 2 diabetes (T2D), unhealthy behaviours are associated with increased risk of cardiovascular disease (CVD) events. To date, little research has considered whether healthy changes in behaviours following T2D diagnosis reduce CVD risk. Methods: A cohort of 867 adults with screen‐detected T2D, participating in the Anglo‐Danish‐Dutch Study of Intensive Treatment in People with Screen‐Detected Diabetes in Primary Care (ADDITION)‐Cambridge trial, were followed for 10 years for incidence of CVD events. Diet, alcohol consumption, moderate/vigorous physical activity and smoking were assessed by questionnaire at the time of T2D screening and 1 year later. We estimated associations between health behaviours and CVD using Cox regression. We assessed modification of the associations by behaviour change in the year following T2D diagnosis. Results: Smoking [hazard ratio (HR): 1.73 (95% CI: 1.04, 2.87)] and high fat intake [HR: 1.70 (95% CI: 1.02, 2.85)] were associated with a higher hazard of CVD, while high plasma vitamin C [HR: 0.44 (95% CI: 0.22, 0.87)] and high fibre intake [HR: 0.60 (95% CI: 0.36, 0.99)] were associated with a lower hazard of CVD. Reduction in fat intake following T2D diagnosis modified associations with CVD. In particular, among those with the highest fat intake, decreasing intake attenuated the association with CVD [HR: 0.75 (95% CI: 0.36, 1.56)]. Conclusion: Following T2D diagnosis, decreasing fat intake was associated with lower long‐term CVD risk. This evidence may raise concerns about low‐carbohydrate, high‐fat diets to achieve weight loss following T2D diagnosis. Further research considering the sources of fat is needed to inform dietary recommendations. Trial registration: This trial is registered as ISRCTN86769081. Retrospectively registered on 15 December 2006.